Features and Shortcomings of the Epic Style in Khavaran Nameh and Bazel’s Hamleh Heidari - Karimi, Sedighe (LANGUAGE ART, 2024)
One of the important functions of stylistics is to study the linguistic features of a literary genre and its changes through history. These changes, which happen as the consequences of conversion of the style, cause the features of the genre to develop or to decline. In its excellent form epic as a literary genre should offer a magnificent content to the readers through vocabulary, compounds, rhetoric and semantic structures. Accordingly, the importance of the present study is to determine the criteria of the epic language and its changes after Shahnameh and from a more precise perspective it has tried to answer the questions: 1- What are the most important features of the epic poetries in Safavi and Teimuri eras? 2- What stylistic factors have caused deficiencies of epic language in these works? This study has been done based on library method , describing and analysing the material collected, focusing on the two works, Ibn-e Hesam’s Khavarannameh and Bazel’s Hamleh Heidari, and it comes to the conclusion that in the epic poetries after Ferdowsi because of the stylistic changes and the impact of individual poets, unfortunately a number of epic language criteria has been neglected; and the factors like rhetoric faults, lack of harmony in the music of rhythm and rhyme, the impact of Arabic language, the influence of colloquial language, unrealistic imaginations and lyric concepts have made deficiencies in its real language. Meanwhile, some of these factors are considered to be stylistic features.